Potassium chloride zinc-iron alloy plating process for magnesium alloy part

By preparing chemical zinc-deposited layer, cyanide-free pre-copper layer, pyrophosphate copper layer and zinc-iron alloy plating layer sequentially on magnesium alloy workpieces, and preparing the sealing layer with hydroxygraphene modified sealing agent, the problem that the nickel layer of magnesium alloy electroplating does not have electrochemical protection is solved, and a magnesium alloy surface protection layer with high corrosion resistance and self-repairability is achieved.

CN119876948AActive Publication Date: 2025-04-25GUANGZHOU ULTRA UNION CHEM LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510038535.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-04-25
Estimated Expiration
2045-01-10

AI Technical Summary

Technical Problem

The electroplating nickel layer of magnesium alloy and the electroless nickel layer have no electrochemical protection effect on the magnesium alloy matrix and there is a large potential difference, which causes the corrosive medium to corrode through the pores of the coating and quickly destroy the magnesium alloy matrix.

Method used

A magnesium alloy potassium chloride galvanized iron alloy process is adopted. After removing oil and pickling and activation of the magnesium alloy workpiece, a chemical zinc deposition layer, a cyanide-free pre-copper layer, a pyrophosphate copper layer, and a zinc-iron alloy plating layer are prepared in turn, and a sealing layer is prepared using hydroxygraphene modified sealant on the zinc-iron alloy plating layer with trivalent chromium passivation.

Benefits of technology

This process effectively prevents corrosion of the corrosion medium toward the magnesium alloy matrix, overcomes the problem that the nickel-plating layer does not have an electrochemical protection effect in the prior art, and the sealing layer prepared by hydroxygraphene modified sealing agent has self-healing properties, improving the corrosion resistance of the magnesium alloy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119876948A_ABST
    Figure CN119876948A_ABST
Patent Text Reader

Abstract

The invention discloses a potassium chloride zinc-iron alloy plating process for a magnesium alloy part. A chemical zinc deposition layer, a cyanide-free copper pre-plating layer, a pyrophosphate copper plating layer, a zinc-iron alloy plating layer, a passive film and a graphene modified sealing layer are sequentially prepared on a magnesium alloy matrix from inside to outside. According to the potassium chloride zinc-iron alloy plating process, 50-70 g / L of zinc chloride, 2-12 g / L of ferrous chloride tetrahydrate, 180-220 g / L of potassium chloride, 25-35 g / L of boric acid, 8-40 g / L of a coordination agent, 0.1-0.2 mL / L of a brightening agent and 20-30 mL / L of an auxiliary agent are adopted, the pH value of a plating solution is 4.5-5.6, the temperature of a plating bath is 15-30 DEG C, the cathode current density is 1-3 A / dm < 2 >, and the cathode movement is 3-5 m / min. According to the magnesium alloy galvanized iron alloy sample piece passivated by trivalent chromium blue and white and sealed by the graphene modified sealing agent, the surface of the magnesium alloy galvanized iron alloy sample piece is free of white rust after being subjected to a neutral salt spray test for 480 h according to the GB / T 10125-2021 standard, and a plating layer has excellent corrosion resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal surface treatment, and in particular relates to a process for plating a magnesium alloy part with potassium chloride zinc and iron alloy. Background Art

[0002] Magnesium alloys have the advantages of high specific strength and specific stiffness, as well as electromagnetic shielding, shock absorption, and good cutting performance. They can be widely used in military, automobile, aircraft, mobile phone, computer, electromechanical and other industrial products, and are known as the "green engineering material of the century". However, magnesium alloys are chemically active, and the oxides generated on their surface are loose and porous, which cannot effectively protect the matrix. Therefore, the development of high corrosion resistance protective layers for magnesium alloys is a research hotspot in the industry.

[0003] There are many methods for magnesium alloy surface treatment, mainly electrophoretic coating, surface plating, micro-arc oxidation, anodizing, chemical conversion film, spraying organic coating and other technologies. [1] However, these surface treatment methods have certain limitations, and the protective effect needs to be further improved. At present, electrophoretic coating technology is mainly used in production applications to prepare a protective layer on the surface of magnesium alloys. This protective layer has relatively good protective performance for magnesium alloy parts.

[0004] The technology of preparing protective layer on magnesium alloy surface by electroplating and chemical plating is still in the research stage. The industry has reported some research on electroplating nickel and chemical plating nickel on magnesium alloy. [2-4] . However, the electroplated nickel layer and chemically plated nickel layer prepared on the surface of magnesium alloy have no electrochemical protection effect on the magnesium alloy substrate, and there is a large potential difference between the substrate and the coating. The electroplated nickel layer and chemically plated nickel layer prepared by the prior art usually contain a certain number of pores. The corrosive medium passes through the pores of the coating to cause galvanic corrosion and quickly destroy the magnesium alloy substrate. Therefore, there is no mass production application report of this electroplating technology for magnesium alloy.

[0005] The hydroxy graphene modified sealant developed and applied in recent years has made great progress in improving the corrosion resistance of the coating. The prepared sealing layer has self-healing properties. [5] It is used to seal the zinc coating and zinc-nickel alloy coating that have been passivated with trivalent chromium, solving the problem that trivalent chromium passivation does not have self-repairing properties.

[0006] References: [1]. Fu Haifeng, Lv Dongxian, Tan Huachao, et al., Research status and trends of magnesium alloy surface modification technology [J], Heat Treatment, 2015, 30(3): 1-5. [2]. Yu Gang, Yi Xiangrong, Lei Xiping, et al., Research on the formation mechanism and electroplating process of nickel electrodeposition on magnesium alloy [J], Electroplating and Environmental Protection, 2009, 29(1): 21-25. [3]. Zhang Xiaohuan, Feng Lajun, Lu Man, Optimization of chemical nickel-phosphorus plating process and research on coating performance on magnesium alloy surface [J], Materials Protection, 2022, 55(6): 86-91. [4]. Xu Gang, Zhang Xiuzhi, Zhang Yishuai, Preparation and performance research of Ni-P / Ni coating on magnesium alloy surface [J], Surface Technology, 2010, 39(1): 71-73+80. [5]. Guo Chongwu, Lai Huanwen, Xia Liang, Research on the performance of graphene oxide in coating sealant[J], Electroplating & Finishing, 2021, 40(9): 696-700. Summary of the invention

[0007] In order to solve the problem of poor corrosion resistance of the existing electroplated protective layer of magnesium alloy, the present invention provides a process for potassium chloride zinc-iron alloy plating of magnesium alloy parts. In order to achieve the above purpose, the present invention adopts the following technical solutions: A process for plating magnesium alloy parts with potassium chloride zinc and iron alloy, comprising the following steps: (1) Degreasing, pickling and activation of magnesium alloy workpieces; (2) After the magnesium alloy workpiece is pre-treated, the chemical zinc deposition layer is prepared by using the current magnesium alloy chemical zinc deposition process; (3) After chemical zinc deposition on the magnesium alloy workpiece, a cyanide-free pre-plated copper layer is prepared by a polymerized thiocyanate copper plating process; (4) The magnesium alloy workpiece is subjected to polythiocyanate copper plating and then the pyrophosphate copper plating layer is prepared by the current pyrophosphate copper plating process; (5) After the magnesium alloy workpiece is pyrophosphate-copper-plated, a zinc-iron alloy coating is prepared by a potassium chloride zinc-iron alloy plating process; (6) After the magnesium alloy workpiece is plated with galvanized iron alloy, it is passivated to prepare a passivation film; (7) After the magnesium alloy workpiece is passivated, it is sealed to prepare a sealing layer; The potassium chloride zinc-iron alloy plating process includes the following components and process parameters: Zinc chloride 50-70g / L, ferrous chloride tetrahydrate 2-12g / L, potassium chloride 180-220g / L, boric acid 25-35g / L, complexing agent 8-40g / L, brightener 0.1-0.2mL / L, auxiliary agent 20-30mL / L, plating solution pH 4.5-5.6, plating tank temperature 15-30℃, cathode current density 1-3A / dm 2, the cathode moves 3-5 m / min, a zinc plate with a mass fraction of 99.9% is used as the anode, and the area ratio of the cathode to the anode is 2:1; in production, a 30% mass fraction of ferrous chloride tetrahydrate solution is added to the plating tank to keep its concentration within the process range; The complexing agent includes sodium gluconate and sodium sulfosalicylate, the mass ratio of sodium gluconate to sodium sulfosalicylate is 3:(1-3), and sodium gluconate and sodium sulfosalicylate are mixed according to the ratio and stirred evenly; The brightener comprises o-chlorobenzaldehyde and formic acid, the mass ratio of o-chlorobenzaldehyde to formic acid is 1:(0.8-1.2), and o-chlorobenzaldehyde and formic acid are mixed in the said ratio and stirred until all the solids are dissolved; The auxiliary agent comprises a sulfonated product of fatty alcohol polyoxyethylene ether with model OX-105 and aminosulfonic acid, sodium benzoate, and nicotinic acid. Calculated by weight, the sulfonated product of fatty alcohol polyoxyethylene ether with model OX-105 and aminosulfonic acid is 17 to 23 parts, sodium benzoate is 5 to 7 parts, nicotinic acid is 0.4 to 0.6 parts, and water is 80 to 90 parts. The above three intermediates are added into water according to the weight fractions and stirred until all the solids are dissolved.

[0008] In some embodiments, the polythiocyanate copper plating process includes the following components and process parameters: Polymeric cuprous thiocyanate 18-24 g / L, polymeric sodium thiocyanate 130-170 g / L, sodium hydroxyethylidene diphosphonate 20-30 g / L, copper plating brightener 8-12 mL / L, plating solution pH 12-13, plating tank temperature 30-40 °C, cathode current density 0.5-1.5 A / dm 2 , the cathode moves 3 to 5 m / min, oxygen-free electrolytic copper particles are used as anodes, the copper particles are placed in a titanium anode basket, the area ratio of anode to cathode is >3:1, and the anode moves 3 to 5 m / min.

[0009] In some of the embodiments, the copper plating brightener comprises the following components in weight fractions: 60-100 parts of N,N'-di-n-propylethylenediamine, 10-20 parts of waterborne polyurethane resin, 80-120 parts of polyacrylamide with a molecular weight less than 8000, and 770-870 parts of deionized water.

[0010] In some embodiments, the pickling activation adopts the following magnesium alloy pickling activation process: Phosphoric acid 23-28 mL / L, ammonium bifluoride 18-22 g / L, room temperature operation, pickling time 50-70 s.

[0011] In some of the embodiments, the chemical zinc deposition layer is prepared by the following magnesium alloy chemical zinc deposition process: Zinc sulfate heptahydrate 25-35g / L, potassium pyrophosphate 100-120g / L, potassium fluoride 6-9g / L, bath temperature 68-72℃, zinc precipitation time 8-12min.

[0012] In some of the embodiments, the passivation film is prepared by TRIROS 348 zinc iron blue-white passivation process: TRIROS 348 zinc iron blue-white passivator 135-175 mL / L, passivation solution pH 2.0-2.8, operating temperature 30-60°C, immersion time 30-60s, air stirring.

[0013] In some of the embodiments, the graphene-modified sealing layer is prepared using PRODICO 480 graphene-modified sealing agent: Dilute PRODICO 480 graphene modified sealer with water to 2.5-3.2 times to prepare the sealing solution. Immerse the plated parts in the sealing solution for 8-15 seconds. Drain after leaving the tank, and use high-pressure air to blow away the sealing solution remaining on the surface of the plated parts. After sealing, dry and cure at 70-80°C for 20-35 minutes.

[0014] In some of the embodiments, the thickness of the zinc-iron coating is 9-16 μm.

[0015] In some of the embodiments, the thickness of the cyanide-free pre-plated copper layer is 2-6 μm.

[0016] In some of the embodiments, the thickness of the pyrophosphate copper plating layer is 10 to 20 μm.

[0017] Compared with the prior art, the present invention has the following beneficial effects: 1. The potassium chloride zinc-iron alloy plating process for magnesium alloy parts of the present invention sequentially prepares a chemical zinc deposition layer, a cyanide-free pre-copper plating layer, a pyrophosphate copper plating layer, and a zinc-iron alloy plating layer on a magnesium alloy substrate. The zinc-iron alloy plating layer is an anodic plating layer relative to the copper plating layer. This plating structure can effectively prevent the corrosive medium from corroding the magnesium alloy substrate, thus overcoming the defects of direct nickel plating after chemical zinc deposition on a magnesium alloy substrate or chemical nickel plating having no electrochemical protection effect; 2. The potassium chloride zinc-iron alloy plating process for magnesium alloy parts of the present invention has a sealing layer prepared by using a hydroxy graphene modified sealing agent on the zinc-iron alloy coating passivated with trivalent chromium, which has self-repairing properties, thus overcoming the defect that the trivalent chromium passivation film has no self-repairing properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] The drawings described herein are used to provide a further understanding of the present invention, constitute a part of the present application, and do not constitute an improper limitation of the present invention. In the drawings: Figure 1It is a schematic diagram of the coating structure of Example 1, Example 2, Example 3 and Example 4 of the present invention. DETAILED DESCRIPTION

[0019] The present invention will be described in detail below in conjunction with the accompanying drawings and specific embodiments. The exemplary embodiments and descriptions of the present invention are used to explain the present invention but are not intended to limit the present invention.

[0020] A potassium chloride zinc-iron alloy plating process for magnesium alloy parts comprises pretreatment of the magnesium alloy workpiece, and sequentially preparing a chemical zinc deposition layer, a cyanide-free pre-plated copper layer, a pyrophosphate copper plating layer, a potassium chloride zinc-iron alloy plating layer, a passivation film, and a graphene modified sealing layer on a magnesium alloy substrate from the inside to the outside.

[0021] The magnesium alloy pretreatment process is used to remove oil, pickle and activate the magnesium alloy workpiece.

[0022] Preferably, the oil removal adopts a weak alkaline ultrasonic oil removal process: Sodium phosphate 20-25g / L, sodium carbonate 20-25g / L, Jintel NP-10 degreasing agent 0.5-1.5g / L, tank temperature 65-75℃, degreasing time 8-12min.

[0023] Preferably, the pickling activation adopts the following pickling activation process: Phosphoric acid 23-28 mL / L, ammonium bifluoride 18-22 g / L, room temperature operation, pickling time 50-70 s.

[0024] After pretreatment of the magnesium alloy workpiece, the chemical zinc deposition layer is prepared by the following magnesium alloy chemical zinc deposition process.

[0025] Zinc sulfate heptahydrate 25-35g / L, potassium pyrophosphate 100-120g / L, potassium fluoride 6-9g / L, bath temperature 68-72℃, zinc precipitation time 8-12min.

[0026] After chemical zinc deposition on the magnesium alloy workpiece, the polymerized thiocyanate copper plating process of the invention is adopted to prepare a cyanide-free pre-plated copper layer.

[0027] Preferably, the thickness of the cyanide-free pre-copper plating layer is 2 to 6 μm.

[0028] Polymeric cuprous thiocyanate 18-24 g / L, polymeric sodium thiocyanate 130-170 g / L, sodium hydroxyethylidene diphosphonate 20-30 g / L, copper plating brightener 8-12 mL / L, plating solution pH 12-13, plating tank temperature 30-40 °C, cathode current density 0.5-1.5 A / dm 2 , the cathode moves 3 to 5 m / min, oxygen-free electrolytic copper particles are used as anodes, the copper particles are placed in a titanium anode basket, the area ratio of anode to cathode is >3:1, and the anode moves 3 to 5 m / min.

[0029] Preferably, the copper plating brightener comprises the following components in weight fractions: 60-100 parts of N,N'-di-n-propylethylenediamine, 10-20 parts of waterborne polyurethane resin, 80-120 parts of polyacrylamide with a molecular weight less than 8000, and 770-870 parts of deionized water.

[0030] Preferably, the copper plating brightener is prepared as follows: 770 to 870 parts by weight of deionized water are added to a reaction tank, 60 to 100 parts of N, N'-di-n-propylethylenediamine, 10 to 20 parts of waterborne polyurethane resin, and 80 to 120 parts of polyacrylamide with a molecular weight less than 8000 are added under stirring, and the brightener is obtained by stirring evenly.

[0031] The magnesium alloy workpiece is subjected to cyanide-free copper plating and then the pyrophosphate copper plating layer is prepared by the current pyrophosphate copper plating process.

[0032] Preferably, the thickness of the pyrophosphate copper plating layer is 10 to 20 μm.

[0033] After the magnesium alloy workpiece is copper plated with pyrophosphate, the zinc-iron alloy plating process with potassium chloride of the present invention is used to prepare the zinc-iron alloy plating layer.

[0034] Preferably, the zinc-iron alloy coating has a thickness of 9 to 16 μm.

[0035] Zinc chloride 50-70g / L, ferrous chloride tetrahydrate 2-12g / L, potassium chloride 180-220g / L, boric acid 25-35g / L, complexing agent 8-40g / L, brightener 0.1-0.2mL / L, auxiliary agent 20-30mL / L, plating solution pH 4.5-5.6, plating tank temperature 15-30℃, cathode current density 1-3A / dm 2 , the cathode moves 3 to 5 m / min, a zinc plate with a mass fraction of 99.9% is used as the anode, and the area ratio of the cathode to the anode is 2:1; during production, a 30% mass fraction of ferrous chloride tetrahydrate solution is added to the plating tank to keep its concentration within the process range.

[0036] The ligand comprises sodium glucose heptanoate and sodium sulfosalicylate, the mass ratio of sodium glucose heptanoate to sodium sulfosalicylate is 3:(1-3), and sodium glucose heptanoate and sodium sulfosalicylate are mixed according to the ratio and stirred evenly.

[0037] The brightener comprises o-chlorobenzaldehyde and formic acid, the mass ratio of o-chlorobenzaldehyde to formic acid is 1:(0.8-1.2), and o-chlorobenzaldehyde and formic acid are mixed according to the ratio and stirred until all solids are dissolved.

[0038] The auxiliary agent comprises a sulfonated product of fatty alcohol polyoxyethylene ether with model OX-105 and aminosulfonic acid, sodium benzoate, and nicotinic acid. Calculated by weight, the sulfonated product of fatty alcohol polyoxyethylene ether with model OX-105 and aminosulfonic acid is 17 to 23 parts, sodium benzoate is 5 to 7 parts, nicotinic acid is 0.4 to 0.6 parts, and water is 80 to 90 parts. The above three intermediates are added into water according to the weight fractions and stirred until all the solids are dissolved.

[0039] The potassium chloride zinc-iron alloy plating solution is prepared as follows: a) Add 70% water into the plating tank according to the volume of the plating solution, add zinc chloride, potassium chloride, boric acid, and complexing agent according to the process requirements, and stir to dissolve the above substances; b) Add ferrous chloride tetrahydrate according to the process requirements and stir until the solid matter is dissolved; c) Add brightener and auxiliary agent according to the process requirements, stir evenly, adjust the pH of the plating solution to the process range with 10% sodium hydroxide solution or 3% hydrochloric acid, and add water to the specified volume; d) at 0.15A / dm 2 The electrolysis was carried out for 60 min at the current density.

[0040] After the magnesium alloy workpiece is plated with galvanized iron alloy, it is prepared by TRIROS 348 zinc iron blue-white passivation process developed by Chaobang Chemical: TRIROS 348 zinc iron blue-white passivator 135-175 mL / L, passivation solution pH 2.0-2.8, operating temperature 30-60°C, immersion time 30-60s, air stirring.

[0041] After the magnesium alloy workpiece was passivated with trivalent chromium, the graphene-modified sealing layer was prepared using PRODICO 480 graphene-modified sealing agent developed by Chaobang Chemical.

[0042] Dilute PRODICO 480 graphene modified sealer with water to 2.5-3.2 times to prepare the sealing solution. Immerse the plated parts in the sealing solution for 8-15 seconds. Drain after leaving the tank, and use high-pressure air to blow away the sealing solution remaining on the surface of the plated parts. After the plated parts are sealed, dry and cure at 70-80°C for 20-35 minutes. Example 1

[0043] like Figure 1 As shown, a potassium chloride zinc-iron alloy plating process for magnesium alloy parts includes pre-treatment of a magnesium alloy substrate 1, and sequentially preparing a chemical zinc deposition layer 2, a cyanide-free pre-plated copper layer 3, a pyrophosphate copper plating layer 4, a potassium chloride zinc-iron alloy plating layer 5, a trivalent chromium passivation film 6, and a graphene modified sealing layer 7 on the pre-treated magnesium alloy substrate 1 from the inside to the outside.

[0044] 1. Pre-treatment: The magnesium alloy workpiece substrate 1 is pre-treated by using the current magnesium alloy pre-treatment process.

[0045] 1) Degreasing: The following weak alkaline ultrasonic degreasing process was used: sodium phosphate 20 g / L, sodium carbonate 20 g / L, Jintel NP-10 degreasing agent 1.2 g / L, tank temperature 70°C, and degreasing time 10 min.

[0046] 2) Pickling activation: The following magnesium alloy pickling activation process was adopted: 25 mL / L phosphoric acid, 20 g / L ammonium bifluoride, room temperature operation, and pickling time of 60 s.

[0047] 2. Chemical zinc precipitation: After the magnesium alloy workpiece is pre-treated, the chemical zinc deposition layer 2 is prepared by the following chemical zinc deposition process.

[0048] Zinc sulfate heptahydrate 30g / L, potassium pyrophosphate 110g / L, potassium fluoride 7g / L, bath temperature 70℃, zinc precipitation time 10min.

[0049] 3. Cyanide-free copper plating: After chemical zinc deposition on the magnesium alloy workpiece, the polythiocyanate copper plating process of the present invention is used to prepare a cyanide-free pre-plated copper layer 3, and the coating thickness is 4 μm.

[0050] 1) Preparation of copper plating brightener: Calculated by weight, 820 parts of deionized water were added to a reaction tank, and 80 parts of N,N'-di-n-propylethylenediamine, 15 parts of waterborne polyurethane resin, and 100 parts of polyacrylamide with model GRO-70 were added under stirring, and stirred evenly to obtain the brightener.

[0051] 2) Plating: Polycuprous thiocyanate 21g / L, sodium polythiocyanate 150g / L, sodium hydroxyethylidene diphosphonate 25g / L, copper plating brightener 10mL / L, plating solution pH 12.5, plating tank temperature 35℃, cathode current density 1.0A / dm 2 , the cathode moves 4m / min, oxygen-free electrolytic copper particles are used as anodes, the copper particles are placed in a titanium anode basket, the area ratio of anode to cathode is >3:1, and the anode moves 4m / min.

[0052] 4. Pyrophosphate copper plating: After the magnesium alloy workpiece is pre-plated with copper without cyanide, a pyrophosphate copper plating process is used to prepare a pyrophosphate copper plating layer 4, and the plating thickness is 15 μm.

[0053] 5. Galvanized iron alloy: After the magnesium alloy workpiece is copper plated with pyrophosphate, the zinc-iron alloy plating process with potassium chloride of the present invention is used to prepare a zinc-iron alloy coating 5, and the coating thickness is 12 μm.

[0054] 1) Preparation of complexing agent: Sodium glucose heptanate and sodium sulfosalicylate are mixed in a mass ratio of 3:2 and stirred evenly to obtain the complexing agent.

[0055] 2) Prepare brightener: The brightener is obtained by mixing o-chlorobenzaldehyde and formic acid in a mass ratio of 1:1 and stirring until all the solids are dissolved.

[0056] 3) Preparation of auxiliary agents: Calculated by weight, 20 parts of the sulfonation product of fatty alcohol polyoxyethylene ether model OX-105 and aminosulfonic acid, 6 parts of sodium benzoate, 0.5 parts of nicotinic acid, and 85 parts of water. Add the above three intermediates into water and stir until the solid matter is completely dissolved to obtain the auxiliary agent.

[0057] 4) Preparation of potassium chloride zinc-iron alloy plating solution: a) Add 70% water into the plating tank according to the volume of the plating solution, add zinc chloride, potassium chloride, boric acid, and complexing agent according to the process requirements, and stir to dissolve the above substances; b) Add ferrous chloride tetrahydrate according to the process requirements and stir until the solid matter is dissolved; c) Add brightener and auxiliary agent according to the process requirements, stir evenly, adjust the pH of the plating solution to 5.4 with 10% by mass sodium hydroxide solution or 3% by mass hydrochloric acid, and add water to the specified volume; d) at 0.15A / dm 2 The electrolysis was carried out for 60 min at the current density.

[0058] 5) Plating: Zinc chloride 65g / L, ferrous chloride tetrahydrate 11g / L, potassium chloride 210g / L, boric acid 30g / L, complexing agent 37g / L, brightener 0.15mL / L, auxiliary agent 25mL / L, plating solution pH 5.4, plating tank temperature 25℃, cathode current density 2A / dm 2 , the cathode moves at 4m / min, the anode is made of 99.9% zinc plate, and the area ratio of cathode to anode is 2:1; during production, 30% ferrous chloride tetrahydrate solution is added to the plating tank to maintain its mass concentration at the required value.

[0059] 6. Passivation: After the magnesium alloy workpiece is plated with galvanized iron alloy, a trivalent chromium passivation film is prepared using the TRIROS 348 zinc-iron blue-white passivation process of Chaobang Chemical 6.

[0060] TRIROS 348 zinc iron blue-white passivator 150mL / L, passivation solution pH 2.4, operating temperature 45℃, immersion time 45s, air stirring.

[0061] The specific process is "film removal with sulfuric acid with a volume fraction of 0.2% → water washing → passivation → water washing → draining after leaving the tank".

[0062] 7. Closure: After the magnesium alloy workpiece is passivated with trivalent chromium, the graphene-modified sealing layer 7 is prepared using PRODICO 480 graphene-modified sealing agent developed by Chaobang Chemical.

[0063] Dilute PRODICO 480 graphene-modified sealer with water to 2.8 times to prepare the sealing solution. Immerse the plated parts in the sealing solution for 10 seconds, drain them after leaving the tank, and use high-pressure air to blow away the sealing solution remaining on the surface of the plated parts. After sealing, dry and cure them at 75°C for 30 minutes.

[0064] Embodiment 2: like Figure 1 As shown, a potassium chloride zinc-iron alloy plating process for magnesium alloy parts includes pre-treatment of a magnesium alloy substrate 1, and sequentially preparing a chemical zinc deposition layer 2, a cyanide-free pre-plated copper layer 3, a pyrophosphate copper plating layer 4, a potassium chloride zinc-iron alloy plating layer 5, a trivalent chromium passivation film 6, and a graphene modified sealing layer 7 on the pre-treated magnesium alloy substrate 1 from the inside to the outside.

[0065] 1. Pre-treatment: The magnesium alloy workpiece substrate 1 is pre-treated by using the current magnesium alloy pre-treatment process.

[0066] 1) Degreasing: The following weak alkaline ultrasonic degreasing process was used: sodium phosphate 25 g / L, sodium carbonate 25 g / L, Jintel NP-10 degreasing agent 0.8 g / L, tank temperature 65°C, and degreasing time 10 min.

[0067] 2) Pickling activation: The following magnesium alloy pickling activation process was adopted: 28 mL / L phosphoric acid, 22 g / L ammonium bifluoride, room temperature operation, and pickling time of 50 s.

[0068] 2. Chemical zinc precipitation: After the magnesium alloy workpiece is pre-treated, the chemical zinc deposition layer 2 is prepared by the following chemical zinc deposition process.

[0069] Zinc sulfate heptahydrate 35g / L, potassium pyrophosphate 120g / L, potassium fluoride 9g / L, bath temperature 68℃, zinc precipitation time 10min.

[0070] 3. Cyanide-free copper plating: After chemical zinc deposition on the magnesium alloy workpiece, the polythiocyanate copper plating process of the present invention is used to prepare a cyanide-free pre-plated copper layer 3, and the coating thickness is 4 μm.

[0071] 1) Preparation of copper plating brightener: Calculated by weight, 820 parts of deionized water were added to a reaction tank, and 80 parts of N,N'-di-n-propylethylenediamine, 15 parts of waterborne polyurethane resin, and 100 parts of IC-113 polyacrylamide were added under stirring, and stirred evenly to obtain the brightener.

[0072] 2) Plating: Polymeric cuprous thiocyanate 24g / L, polymeric sodium thiocyanate 170g / L, sodium hydroxyethylidene diphosphonate 25g / L, copper plating brightener 10mL / L, plating solution pH 12, plating tank temperature 30℃, cathode current density 1.0A / dm 2 , the cathode moves 4m / min, oxygen-free electrolytic copper particles are used as anodes, the copper particles are placed in a titanium anode basket, the area ratio of anode to cathode is >3:1, and the anode moves 4m / min.

[0073] 4. Pyrophosphate copper plating: After the magnesium alloy workpiece is pre-plated with copper without cyanide, a pyrophosphate copper plating layer 4 is prepared by using the existing pyrophosphate copper plating process, and the thickness of the plating layer is 15 μm.

[0074] 5. Galvanized iron alloy: After the magnesium alloy workpiece is copper plated with pyrophosphate, the potassium chloride zinc-iron alloy plating process of the present invention is used to prepare a potassium chloride zinc-iron alloy coating 5, and the coating thickness is 12 μm.

[0075] 1) Preparation of complexing agent: Sodium glucose heptanate and sodium sulfosalicylate are mixed in a mass ratio of 3:2 and stirred evenly to obtain the complexing agent.

[0076] 2) Prepare brightener: The brightener is obtained by mixing o-chlorobenzaldehyde and formic acid in a mass ratio of 1:1 and stirring until all the solids are dissolved.

[0077] 3) Preparation of auxiliary agents: Calculated by weight, 20 parts of the sulfonation product of fatty alcohol polyoxyethylene ether model OX-105 and aminosulfonic acid, 6 parts of sodium benzoate, 0.5 parts of nicotinic acid, and 85 parts of water. Add the above three intermediates into water and stir until the solid matter is completely dissolved to obtain the auxiliary agent.

[0078] 4) Preparation of potassium chloride zinc-iron alloy plating solution: a) Add 70% water into the plating tank according to the volume of the plating solution, add zinc chloride, potassium chloride, boric acid, and complexing agent according to the process requirements, and stir to dissolve the above substances; b) Add ferrous chloride tetrahydrate according to the process requirements and stir until the solid matter is dissolved; c) Add brightener and auxiliary agent according to the process requirements, stir evenly, adjust the pH of the plating solution to 4.6 with 10% sodium hydroxide solution or 3% hydrochloric acid, and add water to the specified volume; d) at 0.15A / dm 2 The electrolysis was carried out for 60 min at the current density.

[0079] 5) Plating: Zinc chloride 70g / L, ferrous chloride tetrahydrate 12g / L, potassium chloride 220g / L, boric acid 35g / L, complexing agent 40g / L, brightener 0.15mL / L, auxiliary agent 25mL / L, plating solution pH 4.6, plating tank temperature 15℃, cathode current density 2A / dm 2 , the cathode moves 4m / min, a zinc plate with a mass fraction of 99.9% is used as the anode, and the area ratio of the cathode to the anode is 2:1; during production, a 30% mass fraction of ferrous chloride tetrahydrate solution is added to the plating tank to keep its concentration within the process range.

[0080] 6. Passivation: After the magnesium alloy workpiece is plated with galvanized iron alloy, a trivalent chromium passivation film is prepared using the TRIROS 348 zinc-iron blue-white passivation process of Chaobang Chemical 6.

[0081] TRIROS 348 zinc iron blue-white passivator 175mL / L, passivation solution pH 2.2, operating temperature 35℃, immersion time 45s, air stirring.

[0082] The specific process is "film removal with sulfuric acid with a volume fraction of 0.2% → water washing → passivation → water washing → draining after leaving the tank".

[0083] 7. Closure: After the magnesium alloy workpiece is passivated with trivalent chromium, the graphene-modified sealing layer 7 is prepared using PRODICO 480 graphene-modified sealing agent developed by Chaobang Chemical.

[0084] Dilute PRODICO 480 graphene-modified sealer with water to 2.8 times to prepare the sealing solution. Immerse the plated parts in the sealing solution for 10 seconds, drain them after leaving the tank, and use high-pressure air to blow away the sealing solution remaining on the surface of the plated parts. After sealing, dry and cure them at 80°C for 20 minutes.

[0085] Embodiment 3: like Figure 1As shown, a potassium chloride zinc-iron alloy plating process for magnesium alloy parts includes pre-treatment of a magnesium alloy substrate 1, and sequentially preparing a chemical zinc deposition layer 2, a cyanide-free pre-plated copper layer 3, a pyrophosphate copper plating layer 4, a potassium chloride zinc-iron alloy plating layer 5, a trivalent chromium passivation film 6, and a graphene modified sealing layer 7 on the pre-treated magnesium alloy substrate 1 from the inside to the outside.

[0086] 1. Pre-treatment: The magnesium alloy workpiece substrate 1 is pre-treated by using the current magnesium alloy pre-treatment process.

[0087] 1) Degreasing: The following weak alkaline ultrasonic degreasing process was used: sodium phosphate 25 g / L, sodium carbonate 20 g / L, Jintel NP-10 degreasing agent 1.0 g / L, tank temperature 70°C, and degreasing time 10 min.

[0088] 2) Pickling activation: The following magnesium alloy pickling activation process was adopted: 26 mL / L phosphoric acid, 20 g / L ammonium bifluoride, room temperature operation, and pickling time of 60 s.

[0089] 2. Chemical zinc precipitation: After the magnesium alloy workpiece is pre-treated, the chemical zinc deposition layer 2 is prepared by the following chemical zinc deposition process.

[0090] Zinc sulfate heptahydrate 25g / L, potassium pyrophosphate 100g / L, potassium fluoride 6g / L, bath temperature 72℃, zinc precipitation time 12min.

[0091] 3. Cyanide-free copper plating: After chemical zinc deposition on the magnesium alloy workpiece, the polythiocyanate copper plating process of the present invention is used to prepare a cyanide-free pre-plated copper layer 3, and the coating thickness is 4 μm.

[0092] 1) Preparation of copper plating brightener: Calculated by weight, 820 parts of deionized water were added to a reaction tank, and 80 parts of N,N'-di-n-propylethylenediamine, 15 parts of waterborne polyurethane resin, and 100 parts of IC-125 polyacrylamide were added under stirring, and stirred evenly to obtain the brightener.

[0093] 2) Plating: Polymeric cuprous thiocyanate 18 g / L, polymeric sodium thiocyanate 130 g / L, copper plating brightener 10 mL / L, plating solution pH 12.5, plating tank temperature 40 ° C, cathode current density 1.0 A / dm 2 , the cathode moves 4m / min, oxygen-free electrolytic copper particles are used as anodes, the copper particles are placed in a titanium anode basket, the area ratio of anode to cathode is >3:1, and the anode moves 4m / min.

[0094] 4. Pyrophosphate copper plating: After the magnesium alloy workpiece is pre-plated with copper without cyanide, a pyrophosphate copper plating layer 4 is prepared by using the existing pyrophosphate copper plating process, and the plating thickness is 15 μm.

[0095] 5. Galvanized iron alloy: After the magnesium alloy workpiece is copper plated with pyrophosphate, the zinc-iron alloy plating process with potassium chloride of the present invention is used to prepare a zinc-iron alloy coating 5, and the coating thickness is 12 μm.

[0096] 1) Preparation of complexing agent: Sodium glucose heptanate and sodium sulfosalicylate are mixed in a mass ratio of 3:2 and stirred evenly to obtain the complexing agent.

[0097] 2) Prepare brightener: The brightener is obtained by mixing o-chlorobenzaldehyde and formic acid in a mass ratio of 1:1 and stirring until all the solids are dissolved.

[0098] 3) Preparation of auxiliary agents: Calculated by weight, 20 parts of the sulfonation product of fatty alcohol polyoxyethylene ether model OX-105 and aminosulfonic acid, 6 parts of sodium benzoate, 0.5 parts of nicotinic acid, and 85 parts of water. Add the above three intermediates into water and stir until the solid matter is completely dissolved to obtain the auxiliary agent.

[0099] 4) Preparation of potassium chloride zinc-iron alloy plating solution: The potassium chloride zinc-iron alloy plating solution is prepared as follows: a) Add 70% water into the plating tank according to the volume of the plating solution, add zinc chloride, potassium chloride, boric acid, and complexing agent according to the process requirements, and stir to dissolve the above substances; b) Add ferrous chloride tetrahydrate according to the process requirements and stir until the solid matter is dissolved; c) Add brightener and auxiliary agent according to the process requirements, stir evenly, adjust the pH of the plating solution to 4.8 with 10% by mass sodium hydroxide solution or 3% by mass hydrochloric acid, and add water to the specified volume; d) at 0.15A / dm 2 The electrolysis was carried out for 60 min at the current density.

[0100] 5) Plating: Zinc chloride 50g / L, ferrous chloride tetrahydrate 8g / L, potassium chloride 180g / L, boric acid 25g / L, complexing agent 28g / L, brightener 0.15mL / L, auxiliary agent 25mL / L, plating solution pH 4.8, plating tank temperature 25℃, cathode current density 2A / dm 2, the cathode moves 4m / min, a zinc plate with a mass fraction of 99.9% is used as the anode, and the area ratio of the cathode to the anode is 2:1; during production, a 30% mass fraction of ferrous chloride tetrahydrate solution is added to the plating tank to keep its concentration within the process range.

[0101] 6. Passivation: After the magnesium alloy workpiece is plated with galvanized iron alloy, a trivalent chromium passivation film is prepared using the TRIROS 348 zinc-iron blue-white passivation process of Chaobang Chemical 6.

[0102] TRIROS 348 zinc iron blue-white passivator 135mL / L, passivation solution pH 2.0, operating temperature 35℃, immersion time 35s, air stirring.

[0103] The specific process is "film removal with sulfuric acid with a volume fraction of 0.2% → water washing → passivation → water washing → draining after leaving the tank".

[0104] 7. Closure: After the magnesium alloy workpiece was passivated with trivalent chromium, the graphene-modified sealing layer was prepared using PRODICO 480 graphene-modified sealing agent developed by Chaobang Chemical.

[0105] Dilute PRODICO 480 graphene-modified sealer with water to 2.8 times to prepare the sealing solution. Immerse the plated parts in the sealing solution for 10 seconds, drain them after leaving the tank, and use high-pressure air to blow away the sealing solution remaining on the surface of the plated parts. After sealing, dry and cure them at 70°C for 35 minutes.

[0106] Embodiment 4: like Figure 1 As shown, a potassium chloride zinc-iron alloy plating process for magnesium alloy parts includes pre-treatment of a magnesium alloy substrate 1, and sequentially preparing a chemical zinc deposition layer 2, a cyanide-free pre-plated copper layer 3, a pyrophosphate copper plating layer 4, a potassium chloride zinc-iron alloy plating layer 5, a trivalent chromium passivation film 6, and a graphene modified sealing layer 7 on the pre-treated magnesium alloy substrate 1 from the inside to the outside.

[0107] 1. Pre-treatment: The magnesium alloy workpiece substrate 1 is pre-treated by using the current magnesium alloy pre-treatment process.

[0108] 1) Degreasing: The following weak alkaline ultrasonic degreasing process was used: sodium phosphate 20 g / L, sodium carbonate 25 g / L, Jintel NP-10 degreasing agent 1.0 g / L, tank temperature 70°C, and degreasing time 10 min.

[0109] 2) Pickling activation: The following magnesium alloy pickling activation process was adopted: 24 mL / L phosphoric acid, 19 g / L ammonium bifluoride, room temperature operation, and pickling time of 65 s.

[0110] 2. Chemical zinc precipitation: After the magnesium alloy workpiece is pre-treated, the chemical zinc deposition layer 2 is prepared by the following chemical zinc deposition process.

[0111] Zinc sulfate heptahydrate 33g / L, potassium pyrophosphate 115g / L, potassium fluoride 8g / L, bath temperature 69℃, zinc precipitation time 9min.

[0112] 3. Cyanide-free copper plating: After chemical zinc deposition on the magnesium alloy workpiece, the polythiocyanate copper plating process of the present invention is used to prepare a cyanide-free pre-plated copper layer 3, and the coating thickness is 4 μm.

[0113] 1) Preparation of copper plating brightener: Calculated by weight, 820 parts of deionized water were added to a reaction tank, and 80 parts of N,N'-di-n-propylethylenediamine, 15 parts of waterborne polyurethane resin, and 100 parts of IC-213 polyacrylamide were added under stirring, and stirred evenly to obtain the brightener.

[0114] 2) Plating: Polymeric cuprous thiocyanate 23g / L, polymeric sodium thiocyanate 165g / L, copper plating brightener 10mL / L, plating solution pH 12.3, plating tank temperature 40℃, cathode current density 1.0A / dm 2 , the cathode moves 4m / min, oxygen-free electrolytic copper particles are used as anodes, the copper particles are placed in a titanium anode basket, the area ratio of anode to cathode is >3:1, and the anode moves 4m / min.

[0115] 4. Pyrophosphate copper plating: After the magnesium alloy workpiece is pre-plated with copper without cyanide, a pyrophosphate copper plating process is used to prepare a pyrophosphate copper plating layer 4, and the thickness of the copper plating layer is 15 μm.

[0116] 5. Galvanized iron alloy: After the magnesium alloy workpiece is copper plated with pyrophosphate, the zinc-iron alloy plating process with potassium chloride of the present invention is used to prepare a zinc-iron alloy coating 5, and the coating thickness is 12 μm.

[0117] 1) Preparation of complexing agent: Sodium glucose heptanate and sodium sulfosalicylate are mixed in a mass ratio of 3:2 and stirred evenly to obtain the complexing agent.

[0118] 2) Prepare brightener: The brightener is obtained by mixing o-chlorobenzaldehyde and formic acid in a mass ratio of 1:1 and stirring until all the solids are dissolved.

[0119] 3) Preparation of auxiliary agents: Calculated by weight, 20 parts of the sulfonation product of fatty alcohol polyoxyethylene ether model OX-105 and aminosulfonic acid, 6 parts of sodium benzoate, 0.5 parts of nicotinic acid, and 85 parts of water. Add the above three intermediates into water and stir until the solid matter is completely dissolved to obtain the auxiliary agent.

[0120] 4) Preparation of potassium chloride zinc-iron alloy plating solution: a) Add 70% water into the plating tank according to the volume of the plating solution, add zinc chloride, potassium chloride, boric acid, and complexing agent according to the process requirements, and stir to dissolve the above substances; b) Add ferrous chloride tetrahydrate according to the process requirements and stir until the solid matter is dissolved; c) Add brightener and auxiliary agent according to the process requirements, stir evenly, adjust the pH of the plating solution to 5.6 with 10% sodium hydroxide solution or 3% hydrochloric acid, and add water to the specified volume; d) At 0.10A / dm 2 The electrolysis was carried out for 90 min at the current density.

[0121] 5) Plating: Zinc chloride 65g / L, ferrous chloride tetrahydrate 11g / L, potassium chloride 210g / L, boric acid 28g / L, complexing agent 36g / L, brightener 0.15mL / L, auxiliary agent 25mL / L, plating solution pH 5.6, plating tank temperature 22℃, cathode current density 2A / dm 2 , the cathode moves 4m / min, a zinc plate with a mass fraction of 99.9% is used as the anode, and the area ratio of the cathode to the anode is 2:1; during production, a 30% mass fraction of ferrous chloride tetrahydrate solution is added to the plating tank to keep its concentration within the process range.

[0122] 6. Passivation: After the magnesium alloy workpiece is plated with galvanized iron alloy, the trivalent chromium passivation film is prepared using the TRIROS 348 zinc-iron blue-white passivation process of Chaobang Chemical.

[0123] TRIROS 348 zinc iron blue-white passivator 165mL / L, passivation solution pH 2.6, operating temperature 55℃, immersion time 35s, air stirring.

[0124] The specific process is "film removal with sulfuric acid with a volume fraction of 0.2% → water washing → passivation → water washing → draining after leaving the tank".

[0125] 7. Closure: After the magnesium alloy workpiece was passivated with trivalent chromium, the graphene-modified sealing layer was prepared using PRODICO 480 graphene-modified sealing agent developed by Chaobang Chemical.

[0126] Dilute PRODICO 480 graphene-modified sealer with water to 2.8 times to prepare the sealing solution. Immerse the plated parts in the sealing solution for 10 seconds, drain them after leaving the tank, and use high-pressure air to blow away the sealing solution remaining on the surface of the plated parts. After sealing, dry and cure them at 77°C for 25 minutes.

[0127] Test Example 1: A neutral salt spray test was carried out in accordance with GB / T 10125-2021 "Salt spray test for corrosion test in artificial atmosphere". The magnesium alloy galvanized iron alloy samples prepared in Example 1, Example 2, Example 3 and Example 4 had no white rust on the surface after 480 hours, and the prepared coating had excellent corrosion resistance.

[0128] Test Example 2: The coating adhesion was tested according to GB / T 5270-2005 "Review of Test Methods for Adhesion Strength of Electrodeposited and Chemically Deposited Metal Coatings on Metal Substrates". The magnesium alloy galvanized iron alloy samples prepared in Example 1, Example 2, Example 3 and Example 4 were placed in a heating furnace and heated to 150°C for 30 minutes. After being taken out, they were immediately placed in room temperature water for cooling. The coating did not blister or fall off, and the coating adhesion met the standard requirements.

[0129] Test Example 3: According to GJB 150.9A-2009 "Military Equipment Laboratory Environmental Test Methods Part 10: Mold Test", a mold test was conducted for 28 days. No mold grew on the surface of the magnesium alloy galvanized iron alloy samples prepared in Example 1, Example 2, Example 3 and Example 4, which met the requirements of industry standards.

[0130] Test example 4: According to GB / T 2423.3-2016 "Basic Environmental Test Procedure for Electrical and Electronic Products Test Ca: Steady State Wet Heat Test Method", a constant humidity test was carried out. The magnesium alloy galvanized iron alloy samples prepared in Example 1, Example 2, Example 3 and Example 4 were tested for 720 hours at a temperature of 40°C and a relative humidity of 93%. There was no visible change in the appearance of the coating, and the coating structure had good weather resistance.

[0131] The technical solutions provided by the embodiments of the present invention are described in detail above. The principles and implementation methods of the embodiments of the present invention are described in detail using specific examples herein. The description of the above embodiments is only applicable to help understand the principles of the embodiments of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which are also considered to fall within the protection scope of the present invention.

Claims

1. A process for potassium chloride zinc-iron alloy plating of magnesium alloy parts, characterized in that: The following steps are involved: (1) Degreasing, pickling and activation of magnesium alloy workpieces; (2) After the magnesium alloy workpiece is pre-treated, the chemical zinc deposition layer is prepared by using the current magnesium alloy chemical zinc deposition process; (3) After chemical zinc deposition on the magnesium alloy workpiece, a cyanide-free pre-plated copper layer is prepared by a polymerized thiocyanate copper plating process; (4) The magnesium alloy workpiece is subjected to polythiocyanate copper plating and then the pyrophosphate copper plating layer is prepared by the current pyrophosphate copper plating process; (5) After the magnesium alloy workpiece is pyrophosphate-copper-plated, a zinc-iron alloy coating is prepared by a potassium chloride zinc-iron alloy plating process; (6) After the magnesium alloy workpiece is plated with galvanized iron alloy, it is passivated to prepare a passivation film; (7) After the magnesium alloy workpiece is passivated, it is sealed to prepare a sealing layer; The potassium chloride zinc-iron alloy plating process includes the following components and process parameters: Zinc chloride 50-70g / L, ferrous chloride tetrahydrate 2-12g / L, potassium chloride 180-220g / L, boric acid 25-35g / L, complexing agent 8-40g / L, brightener 0.1-0.2mL / L, auxiliary agent 20-30mL / L, plating solution pH 4.5-5.6, plating tank temperature 15-30℃, cathode current density 1-3A / dm 2 , the cathode moves 3-5 m / min, a zinc plate with a mass fraction of 99.9% is used as the anode, and the area ratio of the cathode to the anode is 2:1; in production, a 30% mass fraction of ferrous chloride tetrahydrate solution is added to the plating tank to keep its concentration within the process range; The complexing agent includes sodium gluconate and sodium sulfosalicylate, the mass ratio of sodium gluconate to sodium sulfosalicylate is 3:(1-3), and sodium gluconate and sodium sulfosalicylate are mixed according to the ratio and stirred evenly; The brightener comprises o-chlorobenzaldehyde and formic acid, the mass ratio of o-chlorobenzaldehyde to formic acid is 1:(0.8-1.2), and o-chlorobenzaldehyde and formic acid are mixed in the said ratio and stirred until all the solids are dissolved; The auxiliary agent comprises a sulfonated product of fatty alcohol polyoxyethylene ether with model OX-105 and aminosulfonic acid, sodium benzoate, and nicotinic acid. Calculated by weight, the sulfonated product of fatty alcohol polyoxyethylene ether with model OX-105 and aminosulfonic acid is 17 to 23 parts, sodium benzoate is 5 to 7 parts, nicotinic acid is 0.4 to 0.6 parts, and water is 80 to 90 parts. The above three intermediates are added into water according to the weight fractions and stirred until all the solids are dissolved.

2. The process for potassium chloride zinc-iron alloy plating of magnesium alloy parts according to claim 1, characterized in that: The polymerized thiocyanate copper plating process includes the following components and process parameters: Polymeric cuprous thiocyanate 18-24 g / L, polymeric sodium thiocyanate 130-170 g / L, sodium hydroxyethylidene diphosphonate 20-30 g / L, copper plating brightener 8-12 mL / L, plating solution pH 12-13, plating tank temperature 30-40 °C, cathode current density 0.5-1.5 A / dm 2 , the cathode moves 3 to 5 m / min, oxygen-free electrolytic copper particles are used as anodes, the copper particles are placed in a titanium anode basket, the area ratio of anode to cathode is >3:1, and the anode moves 3 to 5 m / min.

3. The process for potassium chloride zinc-iron alloy plating of magnesium alloy parts according to claim 2, characterized in that: The copper plating brightener comprises the following components by weight: 60-100 parts of N,N'-di-n-propylethylenediamine, 10-20 parts of waterborne polyurethane resin, 80-120 parts of polyacrylamide with a molecular weight less than 8000, and 770-870 parts of deionized water.

4. The process for potassium chloride zinc-iron alloy plating of magnesium alloy parts according to claim 1, characterized in that: The pickling activation adopts the following magnesium alloy pickling activation process: Phosphoric acid 23-28 mL / L, ammonium bifluoride 18-22 g / L, room temperature operation, pickling time 50-70 s.

5. The process for potassium chloride zinc-iron alloy plating of magnesium alloy parts according to claim 1, characterized in that: The chemical zinc deposition layer is prepared by the following magnesium alloy chemical zinc deposition process: Zinc sulfate heptahydrate 25-35g / L, potassium pyrophosphate 100-120g / L, potassium fluoride 6-9g / L, bath temperature 68-72℃, zinc precipitation time 8-12min.

6. The process for potassium chloride zinc-iron alloy plating of magnesium alloy parts according to claim 1, characterized in that: The passivation film is prepared by TRIROS 348 zinc iron blue-white passivation process: TRIROS 348 zinc iron blue-white passivator 135-175 mL / L, passivation solution pH 2.0-2.8, operating temperature 30-60°C, immersion time 30-60s, air stirring.

7. The process for potassium chloride zinc-iron alloy plating of magnesium alloy parts according to claim 1, characterized in that: The graphene-modified sealing layer is prepared using PRODICO 480 graphene-modified sealing agent: Dilute PRODICO 480 graphene modified sealer with water to 2.5-3.2 times to prepare the sealing solution. Immerse the plated parts in the sealing solution for 8-15 seconds. Drain after leaving the tank, and use high-pressure air to blow away the sealing solution remaining on the surface of the plated parts. After sealing, dry and cure at 70-80°C for 20-35 minutes.

8. The process for potassium chloride zinc-iron alloy plating of magnesium alloy parts according to claim 1, characterized in that: The thickness of the potassium chloride zinc iron coating is 9-16 μm.

9. The process for potassium chloride zinc-iron alloy plating of magnesium alloy parts according to claim 1, characterized in that: The thickness of the cyanide-free pre-plated copper layer is 2-6 μm.

10. The process for potassium chloride zinc-iron alloy plating of magnesium alloy parts according to claim 1, characterized in that: The thickness of the pyrophosphate copper plating layer is 10-20 μm.

Citation Information

Patent Citations

  • Galvanized iron (vanadium) alloy process of acid system

    CN101922028A

  • NdFeB permanent magnet nickel plating process

    CN119082817A

  • Plating structure of galvanized iron alloy for aluminum alloy part

    CN219886208U